Pengaruh perencanaan pajak dan capital intensity terhadap nilai perusahaan - Alamsah, Jenal; Adi, Ahmad Eko (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The financial statements of a company, especially a public company, are information from a financial perspective for interested parties, especially potential investors who are interested in investing. One reference for investment decisions is the measurement of various company performance indicators. One of the company's performance indicators is Return On Assets where net income is compared with the company's total assets, so that information is obtained on how effective the company is in utilizing assets to earn its income. This study aims to determine the effect of Tax Planning and Capital Intensity on Company Value with a population of eleven mining and other mineral sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. Purposive sampling method was used for sampling, while for analysis using inferential parametric statistics. The results of the study reveal that partially tax planning has no significant effect on firm value and capital intensity has a significant effect on firm value. While simultaneously these variables have a significant effect with a contribution of 30% influence.